Problems of implementation of compulsory health insurance in Ukraine - Vadym Aleksandrov; Pavlo Rubanov; Madi Mazhed Eisa (Health Economics and Management Review)
This article summarizes the arguments and counterarguments within the scientific discussion on health care financing by introducing compulsory health insurance in Ukraine and improving voluntary one. The study's primary purpose is to theorize and determine the main directions and recommendations for implementing compulsory health insurance in Ukraine. Systematization of scientific background concerning the study problem showed that Ukrainian national and municipal health care institutions didn't provide free medical care in the amount and quality guaranteed by the Constitution of Ukraine. Therefore, the relevance of solving this scientific issue is the necessity of comprehensive health care reforming (especially funding) considering compulsory health insurance. To achieve this goal, the study was conducted in the following logical sequence: analyzing models, historical experience, and a hybrid budget insurance system of health care financing; identifying the Ukrainian health insurance features during the pandemic in 2020; clarifying the problems of health insurance development in Ukraine and the world; analyzing and considering the theoretical base on solving health insurance issues; retrospective analysis of the three-level insurance model; developing the practical recommendations for improving the mechanisms of compulsory health insurance implementation. The methodological tools of the study were the methods of dialectical scientific knowledge, systematic approach, statistical and comparative analysis, a review of scientific background, regulatory framework, and insurance companies' reports. The study involves data for 2002-2021. The object of the study is the health insurance system and state mechanisms for regulating compulsory and voluntary health insurance in Ukraine. The obtained results showed that the introduction of compulsory health insurance in Ukraine addressed the expanding availability of medical services to the general population and attracting additional resources in health care. The study empirically confirms and theoretically proves that the Ukrainian government should determine the main health services provided and the insurance premium amount, coordinate the interaction between insurance parties, resolve conflict situations, provide the legal basis for the system functioning, control financial flows and activity insurance fund. The study results can be helpful for insurance market professionals, financiers, and economists in the health care industry, researchers, and students of economic specialties.